Beginning Google Glass Development - Tang, Jeff (Apress : Imprint: Apress, 2014)
Beginning Google Glass Development is your number one resource for learning how to develop for Google Glass--the paradigm-shifting mobile computing platform taking the world by storm now and for years to come. Mobile developers have always had to think for the future, and right now that means getting started with Google Glass. This book is incredibly hands-on with many exciting projects. You will learn the basics of Glass and how to set up your development environment, through to every Glass development topic using Glass Development Kit (GDK): • Glass User Interface • Camera and Image Processing • Video: Basics and Applications • Voice and Audio • Network, Bluetooth, and Social • Locations, Map, and Sensors • Graphics, Animation, and Games You will also learn how to develop enterprise and web-based Glass apps using the Mirror API. Each topic is full of examples that illustrate what Glass can truly do and help you quickly start developing your own apps. Jeff Tang has successfully developed mobile, web, and enterprise apps on many platforms, and cares immensely about user experience. He brings his vast knowledge to this book through cool and practical examples, which will excite and tantalize your creativity. This book is for any developer who is keen to start developing for Glass with GDK or the Mirror API. Whether you are an Android, iOS, web, or enterprise developer, you do not want to miss the chance that Glass becomes the next big thing. Get started with Beginning Google Glass Development and be inspired today.